Hydrodynamics and heat transfer coefficients during CO2 carbonation reaction in a circulated fluidized bed reactor using 200 kg potassium-based dry sorbent. (15th February 2020) - Nam, Hyungseok; Won, Yooseob; Kim, Jae-Young; Yi, Chang-Keun; Park, Young Cheol; Woo, Jae Min; Jung, Su-Yeong; Jin, Gyoung-Tae; Jo, Sung-Ho; Lee, Seung-Yong; Kim, Hyunuk; Park, Jaehyeon
Abstract: Dry sorbent CO2 capture process is a proven technology to remove CO2 efficiently from flue gas. The current system was used to understand the effect of solid inlet height (Hin ) and horizontal heat transfer tubes on solid hydrodynamics in the fast fluidized bed (FFB). Also, the ranges of stable hydrodynamic conditions were visually confirmed at the varied Hin, gas velocity (Ug ) and solid circulation rate (Gs ). The changes in the suspension density (ρsus ) during CO2 carbonation reaction was experimentally measured and matched to the ρsus at the specific gas velocity under no reaction bed. It showed that the ρsus at the initial Ug  = 1.4 m/s under the reaction mode increased to that at 1.04 m/s along the bed due to the carbonation reaction. Heat transfer coefficients (HTC) were obtained during CO2 carbonation operation over 80 h, which resulted in CO2 removal efficiency (85%) and CO2 purity (96%). Finally, the effect of ρsus was determined to be the most significant factor on HTCs, ranged from 135 to 215 W/m 2 ∙ o C during the carbonation reaction. It indicated that the different local HTCs at different bed heights were observed at the carbonation or no reaction modes due to the exothermic reaction heat. Graphical abstract: Image 1 Highlights: Hydrodynamics in FB reactor during CO2 carbonation reaction was investigated. Over 80 h of carbonation reaction was conducted. Above 84% average CO2 removal efficiency with 95% CO2 purity was achieved. Suspension density and Tcw in FB reactor were important factors determining HTC. Higher HTC was ranged from 135 to 215 W/m 2 - o C at different conditions.